Bipolar and Goldenhar: A Case Report of Bipolar Disorder with Psychotic Features in a Man with Goldenhar Syndrome - Shahrbabaki, Mahin Eslami; Pooyanfard, Roya; Abdi, Mohammadamin (Archives of Case Reports, 2023)
Background: Goldenhar syndrome is a congenital condition primarily affecting eye, ear, and spine development. In some cases, it can also impact the heart, lungs, kidneys, and central nervous system. The exact cause of Goldenhar syndrome is not fully understood, and its incidence is estimated to range from 1 in 3500 to 1 in 5600 live births. While intellectual disability is associated with the condition, no established link exists between Goldenhar syndrome and psychiatric disorders. Case presentation: In the presented case, a patient with Goldenhar syndrome has been diagnosed with an episode of mania with psychotic features in the context of bipolar disorder. The patient had no history of prior mental disorders and had an independent life. Discussion: There are few case reports of Goldenhar syndrome patients with mental disorders. In all instances, including our own case, patients exhibited psychotic features during psychiatric examinations. Conclusion: Based on the studies cited and our own research, it is recommended to further investigate the potential association between this syndrome and psychiatric disorders. The following sections provide details on the examination, medical history, and treatment of this patient.